Validation of the Brazilian Portuguese version of the Premenstrual Symptoms Screening Tool (PSST) and association of PSST scores with health-related quality of life - Câmara,Rachel de A. (2017)
Objective: To develop and validate a Brazilian Portuguese version of the Premenstrual Symptoms Screening Tool (PSST), a questionnaire used for the screening of premenstrual syndrome (PMS) and of the most severe form of PMS, premenstrual dysphoric disorder (PMDD). The PSST also rates the impact of premenstrual symptoms on daily activities. Methods: A consecutive sample of 801 women aged ≥ 18 years completed the study protocol. The internal consistency, test-retest reliability, and content validity of the Brazilian PSST were determined. The independent association of a positive screen for PMS or PMDD and quality of life determined by the World Health Organization Quality of Life instrument-Abbreviated version (WHOQOL-Bref) was also assessed. Results: Of 801 participants, 132 (16.5%) had a positive screening for PMDD. The Brazilian PSST had adequate internal consistency (Cronbach’s alpha = 0.91) and test-retest reliability. The PSST also had adequate convergent/discriminant validity, without redundancy. Content validity ratio and content validity index were 0.61 and 0.94 respectively. Finally, a positive screen for PMS/PMDD was associated with worse WHOQOL-Bref scores. Conclusions: These findings suggest that PSST is a reliable and valid instrument to screen for PMS/PMDD in Brazilian women.